Advancing drug safety and mitigating health concerns: High-resolution mass spectrometry in the levothyroxine case study - Hana Chmelařová; Maria Carmen Catapano; Jean-Christophe Garrigues; František Švec; Lucie Nováková (Elsevier, 2024)
Levothyroxine is a drug with a narrow therapeutic index. Changing the drug formulation composition or switching between pharmaceutical brands can alter the bioavailability, which can result in major health problems. However, the increased adverse drug reactions have not been fully explained scientifically yet and a thorough investigation of the formulations is needed.In this study, we used a non-targeted analytical approach to examine the various levothyroxine formulations in detail and to reveal possible chemical changes. Ultra-high-performance liquid chromatography coupled with a data-independent acquisition high-resolution mass spectrometry (UHPLC-DIA-HRMS) was employed.UHPLC-DIA-HRMS allowed not only the detection of levothyroxine degradation products, but also the presence of non-expected components in the formulations. Among these, we identified compounds resulting from reactions between mannitol and other excipients, such as citric acid, stearate, and palmitate, or from reactions between an excipient and an active pharmaceutical ingredient, such as levothyroxine-lactose adduct. In addition to these compounds, undeclared phospholipids were also found in three formulations. This non-targeted approach is not common in pharmaceutical quality control analysis. Revealing the presence of unexpected compounds in drug formulations proved that the current control mechanisms do not have to cover the full complexity of pharmaceutical formulations necessarily.